ChemInform Abstract: An Efficient and Convenient Synthesis of Unsymmetrical Disulfides from Thioacetates. Issue 15 (15th April 2014) - Lach, Slawomir; Demkowicz, Sebastian; Witt, Dariusz
Abstract Reaction of phosphorinanyl‐disulfanyl derivatives (I) with thioacetates (II) in the presence of NaOMe or BuNH2 as the base offers a convenient method for the synthesis of unsymmetrical disulfides.